PERAN AUDITOR INDEPENDEN DALAM MELAKUKAN PEMERIKSAAN LAPORAN KEUANGAN PERSEROAN SEBAGAI UPAYA PERLINDUNGAN HUKUM PEMEGANG SAHAM DARI ITIKAD BURUK DIREKSI - Omar Akbar Aldian Pinem; Sunarmi Sunarmi; Keizerina Devi Azwar; Mahmul Siregar (Universitas Sumatera Utara, 2014)
ABSTRACT Board of directors has an obligation to make an annual report and financial report as the responsibility of the board of directors to stock holders. The audit on financial report functions to guarantee the content of the reports which have been presented properly and in accordance with the general accountancy principle. The presentation of correct financial report is an attempt to protect the interest of stock holders of a certain company. The legal provisions have regulated the implementation of audit on financial report of a company in Indonesia which is an attempt to guarantee the naturalness of the report. An Auditor is a professional who provides his service to gather auditing evidence as the support in expressing his idea on the naturalness of a financial report. An auditor is responsible for his profession, criminal law, administration, and civil law on what he says when it harms other people. The presentation of accurate and true financial statement is a good will of direction in manage the company while manipulation of content of financial statement that cause the loss to the shareholder is a bad will of direction in manage the company that can be prevented by auditing on financial statement. Auditor has a role to appraise the presented financial statement by fulfill the transparancy and accountability as protection to be interest of shareholder especially on the interest or oppeness of material information and in order obtain the accurate statement.. Keywords: Financial Report, Audit, and Protection for Stock Holders